Difference of Right Ventricular Systolic Function Before and After Hemodialysis in Chronic Kidney Disease Stage V In RSD dr. Soebandi Jember - Saskia Mediawati; Suryono Suryono; Enny Suswati (Journal of Agromedicine and Medical Sciences, 2018)
End stage renal disease is a clinical state with an irreversible chronic decreasing function of renal that need a hemodialysis or renal transplant as theraphy. One of the complication of End stage renal disease is cardiovascular. Cardiovascular complication is a major cause of mortality and mobility in End stage renal disease by 44% in Indonesia. Systolic function of right ventricle can be used to assess the heart function. The purpose of this study is to differentiate the systolic function of right ventricle in patient with end stage renal disease in RSD dr. Soebandi Jember. We used analytical observational approach with cross sectional method held at Dialysis and Echocardiography Unit of RSD dr. Soebandi Jember from September to November 2017. Thirty patients with end stage renal disease who routinely undergoes dialysis were observed. Shapiro-Wilk test results 0,000 significance shows that the data is not normally distribute. Wilcoxon test results significance level 0,005 which shows there is a differentiation between before and after hemodialysis of systolic function in end stage renal disease patients of RSD dr. Soebandi Jember. Keywords : End stage renal disease, systolic function on right ventricle, hemodialysis